2020
DOI: 10.1155/2020/9786367
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acupuncture on Muscle Endurance in the Female Shoulder Joint: A Pilot Study

Abstract: Shoulder joint dysfunction is the leading cause of decreased athletic ability in athletes. Shoulder joint sports injuries affect the athletic performance of athletes. Improvements in the muscle endurance of the shoulder joint can reduce the incidence of shoulder joint dysfunction. Acupuncture has been an important part of Asian culture for a long time. In acupuncture, nerves are stimulated, inducing postactivation potentiation (PAP) in the body’s motor units and enhancing muscle strength. In this research, 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…The selected acupoints include: LI14, SJ14, SJ13, LU1, LU4, LU3 and SJ12 [ 7 ]. These points positions are shown in Figure 4 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The selected acupoints include: LI14, SJ14, SJ13, LU1, LU4, LU3 and SJ12 [ 7 ]. These points positions are shown in Figure 4 .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, acupuncture is particularly important in treating diseases, relieving pain and restoring health. Past studies found that acupuncture at specific acupoints can induce parasympathetic excitation of the body and produce “De Qi” [ 4 , 5 , 6 , 7 ], “De Qi” is thought to be caused by myosin regulating light chain phosphorylation in connective tissue fibroblasts that alters the increased sensitivity of actin and myosin Ca2+ to enhance strengthening of the muscles [ 8 ]. Therefore, acupuncture increases the body’s ability to quickly recover from fatigue and improves muscle strength.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study of the effect of acupuncture on the endurance of the female shoulder joint muscles, it was found that acupuncture can increase the excitability of the shoulder joint muscles, delaying muscle fatigue, and increasing muscle endurance [ 22 ]. However, the effectiveness in increasing the explosive force of the female shoulder joint has not been confirmed until now.…”
Section: Introductionmentioning
confidence: 99%